(untitled) (KULT_online, 2017)
Theodore R. Weeks presents his textbook Vilnius Between Nations 1795 – 2000 as a transnational history of Vilnius. The book is based on a large variety of sources and provides a valuable overview of the past 200 years. The author vividly describes ethnic cohabitation and collaboration as well as struggles and destruction. Thereby he makes use of national categories while emphasizing the city’s historical fragility. Writing this book, Weeks partially returns to subjects and regions of his former studies. His approach convincingly combines aspects of social and cultural history while contextualizing findings within a broader political history. Informed by a modern history of space the author engages topographical developments such as memorials and street names and juxtaposes them with contemporary historiographical narratives.